RESPONSIVENESS OF STATE AND RESPONSE ENTROPY AND ALGESIOMETRY DURING INTRAVENOUS FENTANYL ADMINISTRATION: A COMPARISON BETWEEN MALE AND FEMALE PATIENTS - Paighan, Kalyani J; Jonnavithula, Nirmala; Muddamalla, Reetham; Jyothi, Achutuni; Durga, Padmaja (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objectives: The aim of the study was to assess the gender difference in response to fentanyl on the entropy and algesiometry and to compare hemodynamic difference in between the gender. Methods: It was a prospective observational study carried out in a group of 100 patients, of which 50 were males and 50 females. In both the groups, baseline entropy (response entropy [RE] and state entropy [SE]) and algesiometry values were recorded, 2 mic/kg of fentanyl was administered, and entropy values were recorded for 5 min and another algesiometry reading was taken at the end of 5 min. Results: Both the groups were found to be comparable age and weight (p<0.05). However, the mean height of male patients was found to be more as compared to females, and the difference was found to be statistically significant (p=0.037). There was no statistically significant difference in the American society of anesthesiologists grades of male and female patients (p=1). Comorbidities were analyzed using Pearson’s Chi-square test and both the groups were comparable in terms of distribution of comorbidities. (p=1.000). All parameters such as heart rate, systolic blood pressure, diastolic blood pressure, mean arterial pressure, oxygen Saturation, RE, and SE at various time intervals were found to be comparable in male and female patients. There was no statistically significant difference in any of the parameters till 5 min after fentanyl administration (p>0.05). There was no significant difference in entropy values among males and females before and after fentanyl administration. Females had significantly (p=0.033) lower pain threshold and a statistically significant increase in pain threshold as compared to males after fentanyl administration (p=0.012). Conclusion: We conclude that fentanyl administration has not influenced the entropy values based on gender and females had an initial low pain threshold and a greater increase in pain threshold after fentanyl administration.